Solid-state battery cell and method of manufacturing the same, battery device, power using device
Patent Information
- Application Number
- CN202611178525.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-06-16
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
但是固态电池单体中的固-固界面问题严重,由此影响了固态电池单体的性能
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] Cross-references to related applications This application claims priority to Chinese Patent Application No. 202610873236.9, filed on June 16, 2026, entitled “Solid-state battery cell and preparation method thereof, battery device, power device”, the entire contents of which are incorporated herein by reference. Technical Field
[0002] This application relates to a solid-state battery cell and its preparation method, a battery device, and an electrical device. Background Technology
[0003] Compared to battery cells using liquid electrolytes, solid-state battery cells use solid electrolytes, which reduces the risk of combustion and explosion, resulting in high reliability and high energy density. However, the solid-solid interface in solid-state battery cells presents significant challenges, thus affecting their performance. Summary of the Invention
[0004] This application provides a solid-state battery cell and its preparation method, battery device, and power-consuming device, which can improve the solid-solid interface and enhance the rate performance and cycle life of the solid-state battery cell.
[0005] In a first aspect, embodiments of this application provide a method for preparing a solid-state battery cell, comprising: stacking a positive electrode, a base film, and a negative electrode in sequence and placing them in a housing; injecting a precursor solution containing a fluorinated epoxy resin monomer; applying vibration to the housing; and then performing radiation in-situ curing treatment to polymerize the precursor solution in-situ into a solid electrolyte membrane; and obtaining a solid-state battery cell after encapsulation. The solid-state battery cell includes the positive electrode, the solid electrolyte membrane, and the negative electrode, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode.
[0006] In some embodiments, the frequency of the vibration is 20 kHz to 1 MHz.
[0007] In some embodiments, the duration of the vibration is 1-30 minutes.
[0008] In some embodiments, the vibration includes: providing a microsonic transducer on the outside of the housing to cause the housing to vibrate.
[0009] In some embodiments, the vibration includes placing the housing in an ultrasonic device to cause the housing to vibrate.
[0010] In some embodiments, the radiation in the in-situ curing process includes one or more of gamma-ray radiation and electron beam radiation.
[0011] In some embodiments, the total radiation dose in the in-situ radiation curing process is 20-200 kGy.
[0012] In some embodiments, the fluorinated epoxy resin monomer includes one or more of fluorinated alicyclic epoxy resins, fluorinated bisphenol A type epoxy resins, and fluorinated aliphatic epoxy monomers.
[0013] In some embodiments, the fluorinated alicyclic epoxy resin includes 2,2,3,3-tetrafluorooxetane.
[0014] In some embodiments, the fluorinated bisphenol A type epoxy resin includes one or more of hexafluorobisphenol A type epoxy resin, tetrafluorobisphenol A type epoxy resin, and hexafluorobisphenol A diglycidyl ether.
[0015] In some embodiments, the fluorinated aliphatic epoxy monomer trifluoropropylene oxide and tetrafluoropropyl ether are one or more of these.
[0016] In some embodiments, the precursor solution further includes one or more of a solvent, a lithium salt, and an additive.
[0017] In some embodiments, the solvent comprises one or more of linear carbonates and cyclic carbonates. Optionally, the linear carbonate comprises one or more of ethylene carbonate and propylene carbonate, and the cyclic carbonate comprises one or more of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0018] In some embodiments, the lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
[0019] In some embodiments, the additive includes one or more of vinylene carbonate, propylene sulfite, vinyl sulfate, and fluoroethylene carbonate.
[0020] Secondly, embodiments of this application provide a solid-state battery cell, including a positive electrode, a solid electrolyte membrane, and a negative electrode. The solid electrolyte membrane is located between the positive electrode and the negative electrode, and the solid electrolyte membrane includes a fluorinated epoxy resin. The positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a positive active material, and the positive active material includes a nickel-containing transition metal oxide.
[0021] In some embodiments, the mole fraction of nickel is greater than or equal to 0.8, based on the total number of moles of nickel-containing transition metal oxides.
[0022] Thirdly, embodiments of this application provide a battery device including the solid-state battery cell described in the second aspect.
[0023] Fourthly, embodiments of this application provide an electrical device, including a solid-state battery cell as described in the second aspect or a battery device as described in the third aspect. Detailed Implementation
[0024] To better understand the above-mentioned objectives, features, and advantages of this application, the solution of this application will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0025] Many specific details are set forth in the following description in order to provide a full understanding of this application, but this application may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of this application, and not all embodiments.
[0026] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0027] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0028] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0029] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0030] Unless otherwise specified, in this application, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.
[0031] In this application, the terms "multiple" or "various" refer to two or more kinds of things.
[0032] In the description of the embodiments of this application, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0033] Unless otherwise stated, the test temperature for all parameters mentioned in this application is 25°C.
[0034] The battery cells mentioned in the embodiments of this application are capable of charging and discharging independently. The battery cells may be cylindrical, cuboid, or other shapes, and the embodiments of this application are not limited in this respect.
[0035] The battery apparatus mentioned in the embodiments of this application may include one or more battery cell assemblies for providing voltage and capacity. A battery cell assembly may include multiple battery cells, which are connected in series, parallel, or mixed connections via busbars.
[0036] In some embodiments, a battery cell assembly is typically formed by arranging multiple battery cells.
[0037] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple battery cells together with cable ties.
[0038] In some embodiments, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.
[0039] As an example, the battery cell assembly can be a battery module, and the battery cell assembly can be housed in the housing by fixing the battery module in the housing.
[0040] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple battery cells to the housing.
[0041] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.
[0042] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.
[0043] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.
[0044] The technical solutions described in the embodiments of this application are applicable to various electrical devices that use battery cells or battery devices, such as, but not limited to, electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. Battery cells and battery devices are used to store or provide electrical energy.
[0045] The battery cells provided in the embodiments of this application are lithium-ion battery cells.
[0046] Solid-state lithium-ion battery cells are considered a core direction for next-generation energy storage technology due to their revolutionary potential in energy density and safety. Among them, polymer solid-state electrolytes have emerged as an important technological path due to their excellent flexibility, processability, and interfacial contact capabilities with electrodes. However, their industrial application still faces several fundamental scientific and key technological bottlenecks.
[0047] Currently, the mainstream methods for preparing polymer solid electrolytes can be mainly divided into two categories: physical blending methods ("coating-film formation") and chemical synthesis methods ("in-situ polymerization"). Physical blending typically involves casting a polymer matrix (such as PEO), lithium salt, and inorganic fillers into a film through solution casting or hot pressing. While this method is simple, the resulting electrolyte film is prone to forming discontinuous ion transport channels (i.e., "island structure"), and the polymer crystalline regions severely hinder lithium-ion migration, making it difficult to achieve a room-temperature ionic conductivity exceeding 10. -4 The flow rate is on the order of S / cm. More importantly, the electrolyte membrane prepared by this method has a physical contact with the porous electrode, resulting in a huge solid-solid interface impedance, which becomes the core obstacle limiting the rate performance of the battery.
[0048] To improve interfacial contact, in-situ polymerization has emerged. This method injects liquid monomers / oligomers, lithium salts, and initiators into the battery, and initiates polymerization through heat or light to form a polymer electrolyte network in the electrode pores and gaps. This method can achieve close contact between the electrode and electrolyte, effectively reducing interfacial impedance. However, existing technologies have significant limitations: 1) Thermally initiated polymerization usually requires high temperatures (>60℃), which can easily trigger side reactions on the surface of electrode active materials (especially high-nickel ternary, silicon-carbon, etc.), and may lead to side reactions or uneven distribution of monomers before polymerization; 2) UV-initiated polymerization is limited by the penetration depth of ultraviolet light, making it difficult to achieve uniform and complete curing inside batteries with thick electrodes or complex structures such as stacked / wound cells. It is prone to forming a "gradient polymerization" structure, and photoinitiators need to be added, whose decomposition residues may deteriorate the electrochemical stability of the electrolyte.
[0049] A more fundamental challenge lies in the fact that neither physical blending nor traditional in-situ polymerization can simultaneously achieve uniformity of the electrolyte's three-dimensional network structure, strength of interfacial bonding, and continuity of ion transport at the microscopic scale. This leads to common problems in polymer solid-state batteries, such as poor room-temperature performance, deterioration of interfacial contact during cycling, and performance issues at high voltages (>4.3V vs. Li). + Problems such as insufficient chemical / electrochemical stability of / Li.
[0050] Therefore, developing a novel in-situ preparation technology that can achieve deep, uniform, and controllable polymerization at room temperature or near room temperature without the introduction of small molecule initiators is of great significance for constructing high-performance, high-safety, and long-life polymer solid-state lithium batteries.
[0051] This application provides a method for preparing a solid-state battery cell, comprising: stacking a positive electrode, a base film, and a negative electrode in sequence and placing them in a housing; injecting a precursor solution containing a fluorinated epoxy resin monomer; applying vibration to the housing; and then performing radiation in-situ curing treatment to polymerize the precursor solution in-situ into a solid electrolyte membrane; and obtaining a solid-state battery cell after encapsulation. The solid-state battery cell includes a positive electrode, a solid electrolyte membrane, and a negative electrode, with the solid electrolyte membrane located between the positive electrode and the negative electrode.
[0052] The fluorinated epoxy resin polymer network formed by the curing of the fluorinated epoxy resin monomer of this application has high mechanical strength, wide electrochemical window (>4.5V), and good thermal stability, which can be better adapted to ternary high-nickel cathode active materials, thereby enabling solid-state battery cells to have good energy density and high-temperature cycling performance.
[0053] This application employs vibration treatment after electrolyte injection. The resulting "acoustic flow effect" and "cavitation effect" significantly reduce the surface tension and viscosity of the precursor solution, generating a powerful microjet. This allows the precursor solution to rapidly and fully penetrate into the finest pores of the electrode, dispelling internal air bubbles and ensuring uniform distribution and maximum filling within the three-dimensional space of the electrode. This ensures the uniformity of the subsequently formed polymer solid electrolyte from the source. In particular, vibration facilitates the rapid spreading of the precursor solution on the electrode-affinity surface, further promoting uniform wetting. Subsequently, radiation curing technology is used. Radiation has strong penetrating power and can simultaneously and uniformly initiate monomer polymerization throughout the shell. The in-situ formed three-dimensional polymer network achieves "molecular-level" contact with the electrode active material particles, constructing a continuous and uniform lithium-ion transport channel. This overcomes the shortcomings of weak penetration of ultraviolet light curing and uneven curing by heating. Furthermore, the polymerization process requires no chemical initiators, leaves no residual impurities, and avoids side reactions. Thus, vibration dispersion ensures the initial spatial uniformity of the precursor, while radiation curing achieves overall synchronous curing without destroying this uniformity. The two work together to ensure the uniformity of the electrolyte throughout the entire process from "liquid mixing" to "solid forming," thereby significantly reducing the overall and local interface impedance of the battery and improving the battery's rate performance, cycle life, and consistency.
[0054] In some embodiments, the vibration frequency is 20kHz-1MHz, for example, it can be 20kHz, 50kHz, 100kHz, 200kHz, 300kHz, 400kHz, 500kHz, 600kHz, 700kHz, 800kHz, 900kHz, 1MHz, or any combination of the above values.
[0055] In some embodiments, the duration of vibration is 1-30 minutes, for example, it can be 1 minute, 5 minutes, 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes, 30 minutes, or any range of the above values.
[0056] The embodiments of this application have the above-mentioned vibration parameters, which can make the precursor solution better dispersed in various parts of the electrode.
[0057] In some embodiments, vibration includes: providing a microsonic transducer on the outside of the housing to cause the housing to vibrate.
[0058] In some embodiments, the housing is placed in an ultrasonic device, causing the housing to vibrate.
[0059] In some embodiments, the radiation in the radiation in-situ curing process includes one or more of gamma-ray radiation and electron beam radiation.
[0060] Gamma-ray radiation and electron beam radiation have strong penetrating power and can simultaneously and uniformly induce monomer polymerization in various parts of the battery. This overcomes the shortcomings of weak penetration of ultraviolet light curing and uneven curing by heating, thus enabling the in-situ formed three-dimensional polymer network to achieve better "molecular-level" contact with the electrode active material particles and construct a more continuous and uniform lithium-ion transport channel.
[0061] In some embodiments, the total radiation dose in the in-situ radiation curing process is 20-200 kGy, for example, it can be 20 kGy, 30 kGy, 40 kGy, 50 kGy, 60 kGy, 70 kGy, 80 kGy, 90 kGy, 100 kGy, 110 kGy, 120 kGy, 130 kGy, 140 kGy, 150 kGy, 160 kGy, 170 kGy, 180 kGy, 190 kGy, 200 kGy, or any range of the above values.
[0062] Radiation-initiated polymerization, particularly high-energy electron beam (EB) or gamma-ray radiation, offers a new possible path to solving the aforementioned challenges due to its unique penetrability, room-temperature initiation characteristics, and the advantage of not requiring chemical initiators. However, adapting this technology to complex and precise electrochemical systems, designing matching monomer / electrolyte precursor formulations, and precisely controlling radiation process parameters to simultaneously optimize the bulk electrolyte performance and interfacial properties remain key technological gaps that urgently need to be addressed.
[0063] The radiation in-situ curing process in this application embodiment has the above-mentioned total radiation dose, which can simultaneously optimize the electrolyte bulk performance and interface characteristics, so that the battery cells have better rate performance and cycle performance.
[0064] In some embodiments, the fluorinated epoxy resin monomer includes one or more of fluorinated alicyclic epoxy resins, fluorinated bisphenol A type epoxy resins, and fluorinated aliphatic epoxy monomers.
[0065] The solid-state battery cell provided in this application includes a positive electrode, a solid electrolyte membrane, and a negative electrode. The solid electrolyte membrane is located between the positive electrode and the negative electrode and includes fluorinated epoxy resin. The positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a positive active material and the positive active material includes a nickel-containing transition metal oxide.
[0066] In some embodiments, the mole fraction of nickel is greater than or equal to 0.8, based on the total number of moles of nickel-containing transition metal oxides.
[0067] [positive electrode] In some embodiments, the positive current collector may be a metal foil or a composite current collector. The metal foil may be a pure metal, an alloy, or a surface-treated metal, such as, but not limited to, stainless steel foil, carbon-coated aluminum foil, or aluminum foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. As an example, the metal material may include, but is not limited to, one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene.
[0068] Positive electrode active materials may include those with the general formula Li a Ni b Co c M d O e A f One or more of lithium transition metal oxides and their modified materials. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M may include one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A may include one or more of N, F, S, and Cl. Optionally, 0.6≤b<1, 0.8≤b<1.
[0069] As an example, the positive electrode active material may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2Mn 0.3 O2 (abbreviated as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), LiNi 0.83 Co 0.12 Mn 0.05 O2 (abbreviated as NCM83), LiNi 0.9 Co 0.05 Mn 0.05 O2 (Ni90), LiNi 0.92 Co 0.04 Mn 0.04 O2 (Ni92), LiNi 0.93 Co 0.035 Mn 0.035 O2 (Ni93), LiNi 0.96 Co 0.02 Mn 0.02 O2 (abbreviated as Ni96), LiNi 0.80 Co 0.15 Al 0.05 One or more of O2, LiFePO4, LiMnPO4 and their respective modified materials.
[0070] The modified materials for the above-mentioned positive electrode active materials can be the positive electrode active materials through doping modification and / or surface coating modification.
[0071] During the charging and discharging process, solid-state battery cells undergo Li insertion / extraction and consumption, resulting in varying Li molar content at different discharge states. In the examples of positive electrode active materials described in this disclosure, the Li molar content changes after charge-discharge cycles when these materials are used in solid-state battery cells. Furthermore, the O molar content listed in the examples of positive electrode active materials in this disclosure is only a theoretical value; lattice oxygen release causes changes in the O molar content, and the actual O molar content will also fluctuate.
[0072] In some embodiments, the polymer solid electrolyte may further include an inert filler, which can reduce the crystallinity of the polymer and improve its mechanical properties. Optionally, the inert filler may include, but is not limited to, one or more of TiO2, Al2O3, ZrO2, and SiO2.
[0073] In some embodiments, the positive electrode active material layer further includes a positive electrode conductive agent.
[0074] Optionally, the positive electrode conductive agent may be one or more of the following, including but not limited to superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes (CNTs), graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).
[0075] In some embodiments, the positive electrode active material layer further includes a positive electrode binder.
[0076] Optionally, the positive electrode binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.
[0077] [negative electrode] In some embodiments, the negative electrode may include one or more of lithium, lithium alloy, natural graphite, artificial graphite, mesophase micro carbon spheres, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, and metal oxides.
[0078] In some embodiments, the negative electrode can be a metal sheet, such as a lithium sheet or a lithium alloy sheet.
[0079] Optionally, other elements in the lithium alloy sheet may include, but are not limited to, one or more of In, Mg, Al, Zn, Sn, Ag, Au, Ga, Pt, and Fe.
[0080] Alternatively, the lithium alloy sheet may include, but is not limited to, In-Li alloy sheet, Li-Mg alloy sheet, Li-Al alloy sheet, Li-Zn alloy sheet, Li-Fe alloy sheet, etc.
[0081] In some embodiments, the negative electrode may include a negative electrode current collector and a lithium-based metal layer located on at least one surface of the negative electrode current collector. The lithium-based metal layer may be metallic lithium or a lithium alloy. The negative electrode current collector has two surfaces opposite each other in its thickness direction, and the lithium-based metal layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0082] Optionally, other elements in the lithium alloy may include, but are not limited to, one or more of In, Mg, Al, Zn, Sn, Ag, Au, Ga, Pt, and Fe.
[0083] Alternatively, the lithium alloy may include, but is not limited to, In-Li alloy, Li-Mg alloy, Li-Al alloy, Li-Zn alloy, Li-Fe alloy, etc.
[0084] In some embodiments, the negative electrode may include a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material. The negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0085] Optionally, the negative electrode active material may include, but is not limited to, one or more of the following: natural graphite, artificial graphite, mesophase micro carbon spheres, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, and metal oxides.
[0086] Optionally, the silicon-based material may include, but is not limited to, one or more of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Optionally, the tin-based material may include, but is not limited to, one or more of elemental tin, tin oxide, and tin alloys. Optionally, the metal oxide may include, but is not limited to, one or more of TiO2, MoO2, In2O3, Al2O3, Cu2O, VO2, Ga2O3, Sb2O5, and Bi2O5.
[0087] In some embodiments, the negative electrode active material layer further includes a negative electrode binder.
[0088] Optionally, the negative electrode binder may include, but is not limited to, one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, polyacrylic acid, polymethacrylic acid, sodium polyacrylate, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.
[0089] In some embodiments, the negative electrode active material layer may or may not include a negative electrode conductive agent.
[0090] Optionally, the negative electrode conductive agent may be one or more of the following, including but not limited to superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes (CNTs), graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).
[0091] In some embodiments, the negative electrode may or may not include a solid electrolyte.
[0092] In some embodiments, the solid electrolyte may include one or more of a sulfide electrolyte, a halide electrolyte, an oxide electrolyte, and a polymer electrolyte.
[0093] Optionally, the solid electrolyte may include a sulfide electrolyte.
[0094] Optionally, the sulfide electrolyte may include a material with the molecular formula Li 6+m+l P 1-m M m S 5-n+l N n Y 1-l , a material with the molecular formula Li 10±δ Ge 1-g G g P 2-q Q q S 12-w W w , one or more of Li 4-v Ge 1-v P v S4, Li2S-P2S5-based materials, Li2S-SiS2-based materials, Li2S-MeS-P2S5-based materials, and LiGeGaS-based materials, where 0 ≤ m < 1, 0 ≤ n < 1, -1 < l < 1, M includes one or more elements selected from Ge, Si, Sn, Al, Zr and Sb, N includes one or more elements selected from O, Se and Te, Y includes one or more elements selected from Cl, Br and I, 0 ≤ δ < 1, 0 ≤ g ≤ 1, 0 ≤ q ≤ 2, 0 ≤ w < 1, G includes one or two elements selected from Si and Sn, Q includes Sb, W includes one or more elements selected from O, Se, Te, Cl, Br and I, 0 <v < 1, and Me includes one or more elements selected from Si, Ge, Sn and Al.
[0095] Optionally, the sulfide electrolyte may include a material with the molecular formula Li 6+m+l P 1-m M m S 5-n+l N n Y 1-l .
[0096] As an example, the sulfide electrolyte may include Li6PS5Cl, Li6PS5Br, Li6PS5I, Li6PS5Cl 0.5 Br 0.5 , Li 5.5 PS 4.5 Cl 1.5 , Li 5.5 PS 4.5 Br 1.5Li 10 GeP2S 12 Li3PS4, Li7P3S 11 Li 3.25 Ge 0.25 P 0.75 S4, Li6GaGe2S 10 One or more of them.
[0097] Optionally, the sulfide electrolyte may include Li6PS5Cl, Li6PS5Br, Li6PS5I, or Li6PS5Cl. 0.5 Br 0.5 Li 5.5 PS 4.5 Cl 1.5 Li 5.5 PS 4.5 Br 1.5 Li 10 GeP2S 12 One or more of them.
[0098] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. The metal foil may be a pure metal, an alloy, or a surface-treated metal, such as, but not limited to, stainless steel foil, copper foil, and nickel foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. As an example, the metal layer may include, but is not limited to, one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, and polyethylene.
[0099] The negative electrode can be prepared by a dry process or a wet process.
[0100] [Electrolyte layer] In some embodiments, the electrolyte layer comprises a solid electrolyte.
[0101] In some embodiments, the electrolyte layer may or may not include a binder, depending on the manufacturing process of the solid-state battery cell. Optionally, the binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.
[0102] The electrolyte layer can be prepared by a dry process or a wet process.
[0103] In some embodiments, the solid-state battery cell may further include an outer packaging for accommodating the electrode assembly formed by assembling the negative electrode, electrolyte layer, and positive electrode. The outer packaging may be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging may also be a flexible package, such as a pouch. The material of the flexible package may be plastic, such as one or more of aluminum-plastic film, polypropylene, polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0104] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0105] Example 1 Preparation of positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, vapor-grown carbon fiber (VGCF) and positive electrode conductive agent are mixed evenly at a solid mass ratio of 97:3. Then, 1% of the three components are added as a binder, polytetrafluoroethylene (PTFE). The mixture is heated on a heating table at 80°C and rolled back and forth to form a dry positive electrode active material layer. Then, it is combined with the positive electrode current collector aluminum foil hot roller to obtain the positive electrode sheet.
[0106] Preparation of negative electrode sheet Artificial graphite (anode active material), vapor-grown carbon fiber (VGCF) (anode conductive agent), and styrene-butadiene rubber (SBR) (anode binder) were mixed at a solid mass ratio of 97:1:2. Xylene (solvent) was added and the mixture was stirred thoroughly to obtain anode slurry.
[0107] The negative electrode slurry is coated onto the surface of the negative electrode current collector copper foil, and then dried and cold-pressed to obtain the negative electrode sheet.
[0108] Preparation of precursor solution In an argon-filled glove box, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) solvents were mixed at a mass ratio of 3:7. Then, 1 mol / L lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) were added at a mass ratio of 1:1. 3 wt% fluoroethylene carbonate (FEC) and 2 wt% ethylene sulfate (ethylene sulfate) of the total solvent and lithium salt mass were added and mixed thoroughly to obtain an electrolyte. The electrolyte was then mixed with fluorinated epoxy resin monomer (2,2,3,3-tetrafluorooxetane) at a mass ratio of 100:30 to obtain a precursor solution.
[0109] Preparation of soft-pack solid-state battery cells The negative electrode, polypropylene base film, and positive electrode are stacked sequentially from bottom to top to obtain the electrode assembly. The electrode assembly is then encapsulated in an aluminum-plastic bag. The aforementioned precursor solution is injected into the aluminum-plastic bag. Ultrasonic transducers are attached to both sides of the outer side of the aluminum-plastic bag at a frequency of 40 kHz. The bag is ultrasonically treated for 15 minutes and then sealed under vacuum. The sealed aluminum-plastic bag is then transferred to a sealed bag filled with argon gas. Using industrial Co-60 γ-rays as the irradiation source, the bag is irradiated with a total dose of 100 kGy to complete the in-situ polymerization and curing of the fluorinated epoxy monomer, thus obtaining the soft-pack solid-state battery cell.
[0110] Comparative Example 1 The experimental steps are basically the same as in Example 1, except that the preparation of the soft-pack solid-state battery cells is different, in which ultrasonic dispersion is replaced by static dispersion.
[0111] Preparation of soft-pack solid-state battery cells The negative electrode, the polypropylene base film, and the positive electrode are stacked sequentially from bottom to top to obtain the electrode assembly. The electrode assembly is then encapsulated in an aluminum-plastic bag. The aforementioned precursor solution is injected into the aluminum-plastic bag and left to stand at 45°C for 24 hours, followed by standing at 25°C for another 24 hours. The bag is then sealed under vacuum. The sealed aluminum-plastic bag is then transferred to a sealed bag filled with argon gas. Using industrial Co-60 γ-rays as the irradiation source, the bag is irradiated with a total dose of 100 kGy to complete the in-situ polymerization and curing of the fluorinated epoxy monomer, thus obtaining the soft-pack solid-state battery cell.
[0112] Comparative Example 2 The experimental steps are basically the same as in Example 1, except that the preparation of the soft-pack solid-state battery cell is different. Radiation curing is replaced by thermal curing, and 0.1g of lithium bis(trifluoromethanesulfonyl)imide initiator is added to the precursor solution.
[0113] Preparation of soft-pack solid-state battery cells The negative electrode, polypropylene base film, and positive electrode are stacked sequentially from bottom to top to obtain the electrode assembly. The electrode assembly is then encapsulated in an aluminum-plastic bag. The above-mentioned precursor solution containing 0.1g of initiator bis(trifluoromethanesulfonyl)imide lithium is injected into the aluminum-plastic bag. Ultrasonic transducers are attached to both sides of the outer side of the aluminum-plastic bag at a frequency of 40kHz. The bag is ultrasonically treated for 15 minutes and then sealed under vacuum. The sealed aluminum-plastic bag is then heated and cured at 80°C for 6 hours to complete the in-situ polymerization and curing of the fluorinated epoxy monomer, thus obtaining the soft-pack solid-state battery cell.
[0114] Comparative Example 3 The experimental steps are basically the same as in Example 1, except that the preparation of the soft-pack solid-state battery cells is different. Ultrasonic dispersion is replaced by static dispersion, radiation curing is replaced by thermal curing, and 0.1g of lithium bis(trifluoromethanesulfonyl)imide initiator is added to the precursor solution.
[0115] Preparation of soft-pack solid-state battery cells The negative electrode, the polypropylene base film, and the positive electrode are stacked sequentially from bottom to top to obtain the electrode assembly. The electrode assembly is then encapsulated in an aluminum-plastic bag. The above-mentioned precursor solution containing 0.1g of the initiator bis(trifluoromethanesulfonyl)imide lithium is injected into the aluminum-plastic bag. The bag is then left to stand at 45°C for 24 hours, followed by a second standing at 25°C for 24 hours. The bag is then sealed under vacuum. Finally, the sealed aluminum-plastic bag is heated and cured at 80°C for 6 hours to complete the in-situ polymerization and curing of the fluorinated epoxy monomer, thus obtaining the soft-pack solid-state battery cell.
[0116] Performance testing 1. Cyclic performance testing of solid-state battery cells At 25℃, the solid-state battery cell was charged at a constant current rate of 0.1 C to the charging cutoff voltage of 4.25V, and then charged at a constant voltage until the current was less than or equal to 0.02C. After resting for 30 minutes, it was discharged at a current density of 0.1C to 2.5V (vs. Li+ / Li). The discharge specific capacity at this time was recorded as C1. The solid-state battery cell was cycled for n times at a current density of 0.1C. The discharge capacity at this time was recorded as Cn. The capacity retention rate of the solid-state battery cell after n cycles at a current density of 0.1C was = Cn / C1 × 100%. The number of cycles when the capacity retention rate was 80% was recorded.
[0117] 2. First-cycle discharge capacity test At 25°C, the solid-state battery cells were charged at a constant current rate of 0.1 C to the charging cutoff voltage of 4.25V, then charged at a constant voltage until the current was less than or equal to 0.02C. After resting for 30 minutes, they were discharged at a current density of 0.1C to 2.5V (vs. Li). + / Li), to obtain the first-cycle discharge specific capacity.
[0118] 3. DC Internal Resistance (DCIR) Test At 25℃, a solid-state battery cell was charged at a constant current rate of 0.1 C to the charging cutoff voltage of 3.7V, then charged at a constant voltage rate until the current was less than or equal to 0.02C. After resting for 30 minutes, the voltage U1 (V) was recorded. Then, it was discharged at a constant current rate of 1C for 10 seconds, and the voltage U2 (V) at the end of the 10-second discharge was recorded. The internal resistance of the battery cell = (U1 - U2) / discharge current.
[0119] 4. Maximum temperature difference at the 1C discharge surface (ΔT) At 25℃, a temperature-sensing thermocouple was placed at the center of the battery cell. The solid-state battery cell was charged at a constant current rate of 0.1C to the charging cutoff voltage of 4.25V, and then charged at a constant voltage until the current was less than or equal to 0.02C. After standing for 30 minutes, the temperature T1 (℃) was recorded. Then, it was discharged at a current density of 1C to 2.5V (vs. Li+ / Li). The surface temperature T2 (℃) of the cell was recorded when the discharge ended. The maximum surface temperature difference ΔT during 1C discharge is ΔT = T2 - T1.
[0120] Table 1 As shown in the table above, the embodiments of this application use vibration dispersion and radiation curing, resulting in lower DC internal resistance, longer cycle life, and lower maximum temperature difference at the 1C discharge surface of the battery cells, indicating that the polymer solid electrolyte is more evenly distributed inside the electrode assembly.
[0121] Examples 1-1 to 1-6 The experimental steps are basically the same as in Example 1, the difference being the vibration parameters.
[0122] Table 2 As shown in the table above, different vibration parameters can change the distribution of polymer solid electrolyte inside the electrode assembly, thereby giving solid battery cells different DC internal resistance, cycle life, and maximum surface temperature difference at 1C discharge.
[0123] Examples 2-1 to 2-3 The experimental procedure is basically the same as in Example 1, the difference being the radiation parameters.
[0124] Table 3 As shown in the table above, different total radiation doses can alter the distribution of polymer solid electrolytes within the electrode assembly, resulting in solid-state battery cells having different DC internal resistance, cycle life, and maximum surface temperature difference at 1C discharge.
[0125] Examples 3-1 to 3-3 The experimental steps are basically the same as in Example 1, the difference being the different fluorinated epoxy resin monomers.
[0126] Table 4 As shown in the table above, different fluorinated epoxy resin monomers can change the distribution of polymer solid electrolyte inside the electrode assembly, thereby giving solid battery cells different DC internal resistance, cycle life, and maximum surface temperature difference at 1C discharge.
[0127] The above description is merely a specific implementation of this application. Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the specific working processes of the systems, modules, and units described above can be referred to the corresponding processes in the foregoing method embodiments, and will not be repeated here. It should be understood that the protection scope of this application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this application, and these modifications or substitutions should all be covered within the protection scope of this application.
Claims
1. A method for preparing a solid-state battery cell, characterized in that, include: A positive electrode, a base film, and a negative electrode are stacked sequentially and placed inside a housing. A precursor solution containing fluorinated epoxy resin monomers is injected, the housing is vibrated, and then subjected to in-situ radiation curing, which polymerizes the precursor solution in situ into a solid electrolyte membrane. After encapsulation, a solid-state battery cell is obtained. The solid-state battery cell includes the positive electrode, the solid electrolyte membrane, and the negative electrode, with the solid electrolyte membrane located between the positive electrode and the negative electrode.
2. The preparation method according to claim 1, characterized in that, The frequency of the vibration is 20kHz-1MHz; and / or, The duration of the vibration is 1-30 minutes.
3. The preparation method according to claim 1 or 2, characterized in that, The vibrations include: A micro-acoustic transducer is disposed on the outside of the housing, causing the housing to vibrate; and / or, The housing is placed in an ultrasonic device, causing the housing to vibrate.
4. The preparation method according to claim 1 or 2, characterized in that, The radiation in the radiation-induced in-situ curing process includes one or more of gamma-ray radiation and electron beam radiation; and / or, The total radiation dose in the in-situ radiation curing treatment is 20-200 kGy.
5. The preparation method according to claim 1 or 2, characterized in that, The fluorinated epoxy resin monomer includes one or more of fluorinated alicyclic epoxy resins, fluorinated bisphenol A type epoxy resins, and fluorinated aliphatic epoxy monomers.
6. The preparation method according to claim 5, characterized in that, The fluorinated alicyclic epoxy resin includes 2,2,3,3-tetrafluorooxetane; and / or, The fluorinated bisphenol A type epoxy resin includes one or more of hexafluorobisphenol A type epoxy resin, tetrafluorobisphenol A type epoxy resin, and hexafluorobisphenol A diglycidyl ether; and / or The fluorinated aliphatic epoxy monomers include one or more of trifluoropropylene oxide and tetrafluoropropyl ether.
7. The preparation method according to claim 1 or 2, characterized in that, The precursor solution also includes one or more of a solvent, a lithium salt, and an additive.
8. The preparation method according to claim 7, characterized in that, The solvent comprises one or more linear carbonates and cyclic carbonates; optionally, the linear carbonate comprises one or more ethylene carbonate and propylene carbonate, and the cyclic carbonate comprises one or more dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; and / or, The lithium salt includes one or more of lithium hexafluorophosphate, lithium hexafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide; and / or, The additives include one or more of vinylene carbonate, propylene sulfite, vinyl sulfate, and fluoroethylene carbonate.
9. A solid-state battery cell, comprising a positive electrode, a solid electrolyte membrane, and a negative electrode, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode, characterized in that, The solid electrolyte membrane comprises a fluorinated epoxy resin; The positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes a nickel-containing transition metal oxide.
10. The solid-state battery cell according to claim 9, characterized in that, Based on the total number of moles of nickel-containing transition metal oxides, the mole fraction of nickel is greater than or equal to 0.
8.
11. A battery device, characterized in that, It includes multiple solid-state battery cells as described in claim 9 or 10.
12. An electrical appliance, characterized in that, Includes the solid-state battery cell of claim 9 or 10 or the battery device of claim 11.